Comparison of steer feedlot performance and carcass trait uniformly by method of sorting - Houghton, P.L.; Simms, D.D.; Higgins, James J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Long yearling steers (n=997) of various biological types from two origins were used to test performance and carcass trait uniformity of unsorted cattle, visually sorted cattle, and cattle sorted by ultrasound and hip height. No significant differences (P> .05) in initial backfat uniformity were identified between sorted and unsorted groups; however, very little variation existed across all treatments (.17±.033 in.). Initial backfat had positive linear relationships with initial weight and carcass backfat and negative linear relationships with days on feed and daily gain (P<.05). These data indicate a reliable measurement of initial backfat could be useful for predicting days on feed and/or carcass backfat in long yearling steers, but economic usefulness will depend upon the variability of the cattle and the method of grouping.
Keywords: Beef; Feedlot; Ultrasound; Sorting; Carcass traits